Isolation of Cellulolytic Bacteria from Peat Soils as Decomposer of Oil Palm Empty Fruit Bunch - . Gusmawartati; . Agustian; . Herviyanti; . Jamsari (UNIVERSITY OF LAMPUNG, 2017)
The aim of the research was to find out potential strainsof cellulolytic bacteria isolated from two tropical peat soils and to studythe potency of the isolated bacteria to decompose oil palm empty fruit bunch (EFB). The research was carried out in two stages: (1) isolation of cellulolytic bacteria from peat soils and (2) testing the potency of isolated bacteria to decompose oil palm EFB. The cellulolytic bacteria were isolated from two peat soils, i.e. a natural peat soil (forest) and a cultivated peat soil (has been used as agriculture land). Isolation of cellulolytic bacteria was conducted by preparing a series dilution of culture solutions using a streak plate method in a carboxymethyl cellulose(CMC) selective medium.Isolates that were able to form clear zones surrounding their bacterial colony were further tested to study the potency of the isolates to decompose cellulose in oil palm EFB. The cellulolytic activity of the selected isolates were further determined via production of reducing sugars in an oil palm EFB liquid medium using Nelson-Somogyi method. The results showed that there are six isolates of cellulolytic bacteria that have been identified in two tropical peat soils used in the current study. Two isolates are identified in a natural peat soil (forest) and four isolates are identified in a cultivated peat soil. The isolates collected are identified as Bacillus sp., Pseudomonassp. and Staphylococcus sp. Among the isolates, an isolate of GS II-1 produces the highest concentration of reducing sugars, namely 0.1012 unitmL-1or 101 ppm, indicating that the isolate of GS II-1 is highly potential to decompose oil palm EFB. Therefore, the isolate of GS II-1 can be used as a decomposer in the bio-conversion processes of oil palm EFB.Keywords: isolation, bacteria, cellulolytic, oil palm empty fruit bunch (EFB), peat soil